(untitled) (Jurnal Teknologi (Sciences & Engineering), 2014)
The purpose of this research is to design a low power integrated complementary metal oxide semiconductor (CMOS) detection circuit for charge-modulated field-effect transistor (CMFET) and it is used for the detection of deoxyribonucleic acid (DNA) hybridization. With the available CMOS technology, it allows the realization of complete systems which integrate the sensing units and transducing elements in the same device. Point-of-care (POC) testing device is a device that allows anyone to operate anywhere and obtain immediate results. One of the important features of POC device is low power consumption because it is normally battery-operated. The power consumption of the proposed integrated CMOS detection circuit requires only 14.87 mW. The detection circuit will amplify the electrical signal that comes from the CMFET to a specified level in order to improve the recording characteristics of the biosensor. Self-cascode topology was used in the drain follower circuit in order to reduce the channel length modulation effect. The proposed detection circuit was designed with 0.18Âµm Silterra CMOS fabrication process and simulated under Cadence Simulation Tool.Â